Calf circumference as a surrogate marker of muscle mass for diagnosing sarcopenia in Japanese men and women. Issue 8 (20th September 2014) - Kawakami, Ryoko; Murakami, Haruka; Sanada, Kiyoshi; Tanaka, Noriko; Sawada, Susumu S; Tabata, Izumi; Higuchi, Mitsuru; Miyachi, Motohiko
<x xml:space="preserve">Abstract</x> Aim To examine the relationship between calf circumference and muscle mass, and to evaluate the suitability of calf circumference as a surrogate marker of muscle mass for the diagnosis of sarcopenia among middle‐aged and older Japanese men and women. Methods A total of 526 adults aged 40–89 years participated in the present cross‐sectional study. The maximum calf circumference was measured in a standing position. Appendicular skeletal muscle mass was measured using dual‐energy X‐ray absorptiometry, and the skeletal muscle index was calculated as appendicular skeletal muscle mass divided by the square of the height (kg/m2). The cut‐off values for sarcopenia were defined as a skeletal muscle index of less than −2 standard deviations of the mean value for Japanese young adults, as defined previously. Results Calf circumference was positively correlated with appendicular skeletal muscle (r = 0.81 in men, r = 0.73 in women) and skeletal muscle index (r = 0.80 in men, r = 0.69 in women). In receiver operating characteristic analysis, the optimal calf circumference cut‐off values for predicting sarcopenia were 34 cm (sensitivity 88%, specificity 91%) in men and 33 cm (sensitivity 76%, specificity 73%) in women. Conclusions Calf circumference was positively correlated with appendicular skeletal muscle mass and skeletal muscle index, and could be used as a surrogate marker of muscle mass for diagnosing sarcopenia. The suggested cut‐off values of calf circumference for predicting low muscle mass are <34 cm in men and <33 cm in women. Geriatr Gerontol Int 2015; 15: 969–976.